Integration of ICT in Education in a Secondary School in Kenya: A Case Study - Kisirkoi, Florence (Literacy Information and Computer Education Journal, 2015)
Amidst reports that there was very little integration of Communication Information Technology (ICT) in curriculum delivery in many secondary schools in Kenya, it was reported that one secondary school was using ICT in instruction and practicing learner centered instructional approaches and there was improved learning outcomes. The school’s mean score in the Kenya Certificate of Secondary Education had improved from 6.2 to 8.4 between 2007 and 2013. This study teacher computer literacy levels, motivation for integration, perceived reason for the intervention and the impact on teaching and learning. A case study was conducted and observation and interview schedules were used to collect data. The study population was the 535 students and the 28 teachers in the school. Simple random sampling was used to sample 30 students and 18 teachers. It was established that the students and teachers were computer literate and were able to manage computer applications for teaching and learning. The Learning process was found to be practical with learner interactions and activities based learning. The motivation was desire to teach better coupled with visionary, supportive school leadership. The school was using ICT as teaching learning tool and there was improvement of learning environment and outcomes. Many schools ought to emulate the school.
KerkoCite.ItemAlsoKnownAs: 10.20533/licej.2040.2589.2015.0253 10/gj37fv 2339240:79CQYH29 2405685:BV3P33XH

Inclusive education in an international school: A case study from Hong Kong - Chan, T.; Yuen, Mantak (International Journal of Special Education, 2015)
This case study provides an overview of current policy, practices and problems concerning inclusion in one international secondary school in Hong Kong. A total of 13 interviews were conducted with the school management team, teachers, students and parents, supplemented by 12 classroom observations and two ‘student-shadowing’ exercises. Findings suggest that the school has been reasonably successful in raising teachers’ awareness of inclusive education principles, creating a whole-school culture of inclusiveness, and forming a partnership with parents. However, the commitment of individual teachers to implementation of inclusive practices in their own classrooms varies. Some teachers are not adaptive enough in their teaching approach, and have difficulties differentiating instruction and learning activities. Improvements are also needed in the way that teachers work with their education assistants (classroom aides). Implications for improvement are discussed. © 2015, International Journal of Special Education. All rights reserved.
KerkoCite.ItemAlsoKnownAs: 2339240:G6HTWKIA 2405685:5VS97KU6

Design and development of a Web Based Learning System in lower primary schools: A Case study of Makini Primary School, Kenya - Akinyi, Beatrice Ochieng (Moi University, 2015)
Web design technology arises from continued technological trend of computing. Globally the rise of application of information communication technology to the learning programme of primary schools is not much emphasized on. There is empirical evidence to prove that information communication technology is highly beneficial wherever it is applied. The study aimed at designing and developing a web based system of learning that can enhance the academic and social growth of lower primary school pupils. The objectives of the study were: to examine the correlation between the increased use of web based systems of learning and learner‟s academic performance; to identify the set of skills required for lower primary pupils to fully exploit the potential of web based systems of learning; to find out the specification and technical attributes of web based systems of learning that facilitate learning and lastly to design a web based learning system for lower primary school pupils. The study focused on Makini lower primary school in Nairobi County. The study employed case study method and qualitative approach. Rapid Application Development life cycle was used in software development process. Purposive sampling method was used to identify the respondents. Data was collected using interviews and focus group discussions. Findings of the study were: increased use of web based system that enhanced the learner‟s academic performance, the web based system of learning was able to identify games which exploit the pupils‟ skill in learning hence reducing monotony and lastly the web based system was able to identify some technical attributes such as use of graphics and access rights that facilitated learning and testing. The conclusion showed that developing of a web based learning system would reduce monotony in learning and enabled pupils to be in control and also increased the creativity and thinking level. The study recommends that: additions be made to the system such as a module to generate a feasible master timetable for each teacher; the web application of the system be further expanded to help attendance recording by the class teacher and for the parents to be able to view the status of their children performance using the Internet or Intranet of the school and lastly the system be made for every teacher to have some specific free periods or some part of days off and that will require an efficient search technique.
Accepted: 2018-07-19T06:28:17Z KerkoCite.ItemAlsoKnownAs: 2339240:2NYT4UPN 2339240:9UIGBGDA 2405685:II4IEI4L 2405685:UZS2AQCD
Keywords: ___working_potential_duplicate

Challenges and opportunities for e-learning in education: A case study - Kafyulilo, Ayoub C. (Handbook of Research on Educational Technology Integration and Active Learning, 2015)
This chapter presents a review of literature on the existing opportunities and challenges of adopting e-learning in education in Tanzania and the possible measures to overcome some challenges. The study also assessed the primary factors contributing to the slow and limited use and integration of tec...
Publisher: IGI Global KerkoCite.ItemAlsoKnownAs: 10.4018/978-1-4666-8363-1.ch015 2339240:LU5HVRJJ 2405685:JKIRKBQJ

Evaluation of the application of mobile phone technology in teaching and learning: A case study of Kamwenja Teacher' college, Nyeri County, Kenya. - Gitome, Mwangi Joseph (Mount Kenya University, 2015)
This research was designed to investigate the application of mobile phone technology in teaching and learning among tutors and students of Kamwenja Teachers College in Nyeri County in Kenya. The problem this study addressed was to establish whether mobile phones in the hands of students and tutors were beneficial for teaching and learning or if they impede learning process in Teacher Training Colleges in Kenya. The variables under consideration were: quality teaching and learning as dependent variable and owning mobile phones, awareness of educational potential of mobile phones, acceptance of mobile phones, and mobile phones influence as alternative learning and instructional methods as independent variables. The data was collected from 71 tutors and 498 students. The sample size was worked out at 20% to be 15 tutors and 100 second year teacher trainees in the college. Stratified random sampling was used to ensure the sample was a true representation of the whole population. Data was collected through questionnaires that were both quantitative and qualitative to ensure high quality of information for the study where 98.2% response rate was achieved. To ensure Validity and Reliability of Research Instruments a pre-test of the questionnaire was conducted on tutors and students of Kagumo Teachers College. A reliability coefficient of 0.7 was adopted for the items while an expert, the supervisor, guided in validity of the items. The study was guided by the activity theory also known as Cultural Historical Activity Theory. Primary data was analysed with the aid of Statistical Package for Social Sciences (SPSS version 20) software to generate descriptive statistics, correlation and multiple regression analysis. The findings of the study revealed that ownership of mobile phone had a positive and significant effect on application of mobile phone technology in teaching and learning when considered singly and even when regressed together with other factors. Further, the study revealed that awareness of the educational potential of mobile phone technology, acceptance of mobile phone technology and mobile phone technology as an alternative learning and instructional methods were found to have a positive and significant effect on application of mobile phone technology in teaching and learning when considered singly, however when all the factors were regressed together they were found to have a positive and but insignificant effect on application of mobile phone technology in teaching and learning. In order to enhance use of mobile phone technology in teaching and learning students and teachers should be encouraged to acquire mobile phones with internet connectivity features. The general usage of mobile phone in teachers training colleges was found to be very high. However the rate at which mobile phones are used for exchanging learning information is low. The researcher recommends that policies be put in place on use of mobile phone technology in teaching and learning and train tutors on how to teach differently using mobile phone technology. Future researchers should try to establish hindrances of application of mobile phone technology in teaching and learning.
Accepted: 2016-04-04T13:40:40Z KerkoCite.ItemAlsoKnownAs: 2339240:FXSLMRTK 2405685:6TXKF9WF

Live video classroom observation: an effective approach to reducing reactivity in collecting observational information for teacher professional development - Liang, Jiwen (Journal of Education for Teaching: International Research and Pedagogy, 2015)
This paper examines the significance of live video classroom observations of teaching practice to reduce reactivity (the observer effect) so as to obtain more credible observational information for teacher professional development in a secondary school in the largest city in southern China. Although much has been discussed regarding the use of remote live video classroom observation for professional development, the advantage of remote live video classroom observation in reducing reactivity has often been overlooked. Using the case study method, the research reported here focuses on two components: conducting live video classroom observation and the use of the live video classroom observation in reducing reactivity. This paper suggests that live video classroom observation is effective in reducing reactivity and helps avoid subjective judgement and increase feedback sources, thus providing a solution to compensate for the limitations of traditional classroom observations.
Publisher: Routledge, Available from: Taylor & Francis, Ltd. 325 Chestnut Street Suite 800, Philadelphia, PA 19106 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1720065888?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1080/02607476.2015.1045314 2339240:VQ7H8WUD 2405685:63X8MEP4 2534378:69WEYDDC 2534378:6KGYG6GM 2534378:NCYRP586
Keywords: Administrator Attitudes; Case Studies; Case studies; China; Classroom Observation Techniques; Classroom observation; ERIC; Current Index to Journals in Education (CIJE); Education; Effectiveness; Faculty Development; Feedback; Feedback (Response); Foreign Countries; Interviews; Principals; Professional development; Qualitative Research; Secondary Education; Secondary School Teachers; Secondary schools; Teacher Attitudes; Teacher education; Teaching; Teaching Methods; Teaching methods; Video; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2096967; __finaldtb

Live video classroom observation: an effective approach to reducing reactivity in collecting observational information for teacher professional development - Liang, Jiwen (Journal of Education for Teaching: International Research and Pedagogy, 2015)
This paper examines the significance of live video classroom observations of teaching practice to reduce reactivity (the observer effect) so as to obtain more credible observational information for teacher professional development in a secondary school in the largest city in southern China. Although much has been discussed regarding the use of remote live video classroom observation for professional development, the advantage of remote live video classroom observation in reducing reactivity has often been overlooked. Using the case study method, the research reported here focuses on two components: conducting live video classroom observation and the use of the live video classroom observation in reducing reactivity. This paper suggests that live video classroom observation is effective in reducing reactivity and helps avoid subjective judgement and increase feedback sources, thus providing a solution to compensate for the limitations of traditional classroom observations.
Publisher: Routledge, Available from: Taylor & Francis, Ltd. 325 Chestnut Street Suite 800, Philadelphia, PA 19106 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1720065888?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1080/02607476.2015.1045314 2405685:XGZM5SEC 2534378:69WEYDDC 2534378:6KGYG6GM 2534378:NCYRP586
Keywords: Administrator Attitudes; Case Studies; Case studies; China; Classroom Observation Techniques; Classroom observation; ERIC; Current Index to Journals in Education (CIJE); Education; Effectiveness; Faculty Development; Feedback; Feedback (Response); Foreign Countries; Interviews; Principals; Professional development; Qualitative Research; Secondary Education; Secondary School Teachers; Secondary schools; Teacher Attitudes; Teacher education; Teaching; Teaching Methods; Teaching methods; Video; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2096967; __finaldtb

Live video classroom observation: an effective approach to reducing reactivity in collecting observational information for teacher professional development - Liang, Jiwen (Journal of Education for Teaching: International Research and Pedagogy, 2015)
This paper examines the significance of live video classroom observations of teaching practice to reduce reactivity (the observer effect) so as to obtain more credible observational information for teacher professional development in a secondary school in the largest city in southern China. Although much has been discussed regarding the use of remote live video classroom observation for professional development, the advantage of remote live video classroom observation in reducing reactivity has often been overlooked. Using the case study method, the research reported here focuses on two components: conducting live video classroom observation and the use of the live video classroom observation in reducing reactivity. This paper suggests that live video classroom observation is effective in reducing reactivity and helps avoid subjective judgement and increase feedback sources, thus providing a solution to compensate for the limitations of traditional classroom observations.
Publisher: Routledge, Available from: Taylor & Francis, Ltd. 325 Chestnut Street Suite 800, Philadelphia, PA 19106 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1720065888?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1080/02607476.2015.1045314 2339240:VQ7H8WUD 2405685:63X8MEP4 2534378:69WEYDDC 2534378:6KGYG6GM 2534378:NCYRP586
Keywords: Administrator Attitudes; Case Studies; Case studies; China; Classroom Observation Techniques; Classroom observation; ERIC; Current Index to Journals in Education (CIJE); Education; Effectiveness; Faculty Development; Feedback; Feedback (Response); Foreign Countries; Interviews; Principals; Professional development; Qualitative Research; Secondary Education; Secondary School Teachers; Secondary schools; Teacher Attitudes; Teacher education; Teaching; Teaching Methods; Teaching methods; Video; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2096967; __finaldtb

The Effects of a Technology-Aided Learning Environment on the Improvement of a Primary Special Education School - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people's expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming '"learning" or "effective" schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers' functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed.
Publisher: Academic Journals KerkoCite.ItemAlsoKnownAs: 10.5897/ERR2015.2523 10.5897/err2015.2523 10/gjj9dr 2339240:ZXNUGEXT 2405685:SHM89EW9
Keywords: Academic Achievement; Assistant Principals; Attitude Measures; Case Studies; Cooperation; Educational Innovation; Educational Technology; Elementary Education; Elementary School Teachers; Foreign Countries; Observation; Parents; Principals; Qualitative Research; School Personnel; Semi Structured Interviews; Special Education; Statistical Analysis; Teaching Methods; Technology Uses in Education; ___working_potential_duplicate

The Effects of a Technology-Aided Learning Environment on the Improvement of a Primary Special Education School - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people's expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming '"learning" or "effective" schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers' functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed.
Publisher: Academic Journals KerkoCite.ItemAlsoKnownAs: 10.5897/ERR2015.2523 10.5897/err2015.2523 10/gjj9dr 2339240:ZXNUGEXT 2405685:SHM89EW9
Keywords: Academic Achievement; Assistant Principals; Attitude Measures; Case Studies; Cooperation; Educational Innovation; Educational Technology; Elementary Education; Elementary School Teachers; Foreign Countries; Observation; Parents; Principals; Qualitative Research; School Personnel; Semi Structured Interviews; Special Education; Statistical Analysis; Teaching Methods; Technology Uses in Education; ___working_potential_duplicate

Review of international research on factors underlying teacher absenteeism - Lee, Mary; Goodman, Crystal; Dandapani, Nitara; Kekahio, Wendy (Regional Educational Laboratory Pacific, 2015)
Throughout the U.S.-affiliated Pacific Region, teacher absenteeism has posed a long-standing challenge. This report draws on research literature from international contexts and case studies to identify the underlying factors that may relate to teacher absenteeism. Resources included in this report were selected with a focus on non-U.S. Pacific entities and emerging economy contexts that might be most relevant to the U.S.-affiliated Pacific Islands. Different search parameters were used to determine the scope of U.S./international literature to include in the review. The report found five main themes to consider in relation to teacher absenteeism: pay structure (for example, direct or indirect working relationship with the school), management (for example, school governance), working conditions (for example, school culture or single- vs. multi-grade classroom structure), community conditions (for example, teachers' proximity to the school), and social and cultural responsibilities (for example, illness, funeral attendance, and care of family members). Predictors of absenteeism vary across place and context. Given the diversity of Pacific Region communities, stakeholders should examine the extent to which the context and results of the research in this review correspond to the social, structural, cultural, and environmental characteristics of their own contexts. The following are appended: (1) Data and methodology; and (2) Viewing absenteeism through an international lens. A list of selected literature on teacher absenteeism in the United States is also included.
KerkoCite.ItemAlsoKnownAs: 2405685:Z9V9R7T9 4042040:VY5IMADZ 4556019:D8JJI88Z 4556019:IDEEUGZN
Keywords: Academic Rank (Professional); Accountability; C:LMIC; Case Studies; Community Characteristics; Correlation; Cross Cultural Studies; Cultural Context; Cultural Influences; Elementary School Teachers; Family Work Relationship; Foreign Countries; LMICs; School Administration; School Culture; School Location; Social Influences; Teacher Attendance; Teacher Salaries; Teaching Conditions; Work Environment; ⛔ No DOI found

Review of International Research on Factors Underlying Teacher Absenteeism. - Lee, Mary; Goodman, Crystal; Dandapani, Nitara; Kekahio, Wendy (Regional Educational Laboratory Pacific, 2015)
Throughout the U.S.-affiliated Pacific Region, teacher absenteeism has posed a long-standing challenge. This report draws on research literature from international contexts and case studies to identify the underlying factors that may relate to teacher absenteeism. Resources included in this report were selected with a focus on non-U.S. Pacific entities and emerging economy contexts that might be most relevant to the U.S.-affiliated Pacific Islands. Different search parameters were used to determine the scope of U.S./international literature to include in the review. The report found five main themes to consider in relation to teacher absenteeism: pay structure (for example, direct or indirect working relationship with the school), management (for example, school governance), working conditions (for example, school culture or single- vs. multi-grade classroom structure), community conditions (for example, teachers' proximity to the school), and social and cultural responsibilities (for example, illness, funeral attendance, and care of family members). Predictors of absenteeism vary across place and context. Given the diversity of Pacific Region communities, stakeholders should examine the extent to which the context and results of the research in this review correspond to the social, structural, cultural, and environmental characteristics of their own contexts. The following are appended: (1) Data and methodology; and (2) Viewing absenteeism through an international lens. A list of selected literature on teacher absenteeism in the United States is also included.
Publication Title: Regional Educational Laboratory Pacific KerkoCite.ItemAlsoKnownAs: 2339240:QK98HZNR 2405685:B77I7YF6
Keywords: Academic Rank (Professional); Accountability; Case Studies; Community Characteristics; Correlation; Cross Cultural Studies; Cultural Context; Cultural Influences; Elementary School Teachers; Family Work Relationship; Foreign Countries; Institutional Characteristics; Predictor Variables; Proximity; Sanctions; School Administration; School Culture; School Location; Social Influences; Teacher Attendance; Teacher Salaries; Teaching Conditions; Work Environment

Do No Harm teaching case study: Cité Soleil. Reference for workshop participants - Robillard, Sabina Carlson (CDA Collaborative Learning Projects, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:CBIIBYQ8 2405685:WFMXANTK
Keywords: ⛔ No DOI found

A Social Informatics Analysis of Refugee Mobile Phone Use: A Case Study of Zaaatari Syrian Refugee Camp - Maitland, Carleen; Xu, Ying (SSRN Electronic Journal, 2015)
shortDOI: 10/ghgn4p KerkoCite.ItemAlsoKnownAs: 10/ghgn4p 2405685:EEWN2MQD

Empowering Teachers to Promote Inclusive Education. A case study of approaches to training and support for inclusive teacher practice - Donnelly, Verity (European Agency for Special Needs and Inclusive Education, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:WMMVHIHD 2405685:ERPJWFQ4

A case study of the One Laptop per Child Project in Rwanda: Exploring the socio-cultural dimensions of delivery and implementation. - Girgis, R. (University of Cambridge, Cambridge, UK., 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:LRYTMBME 2405685:NRTNZLBJ

The political economy of bad data: Evidence from African survey and administrative statistics - Sandefur, Justin; Glassman, Amanda (The Journal of Development Studies, 2015)
Across multiple African countries, discrepancies between administrative data and independent household surveys suggest official statistics systematically exaggerate development progress. We provide evidence for two distinct explanations of these discrepancies. First, governments misreport to foreign donors, as in the case of a results-based aid programme rewarding reported vaccination rates. Second, national governments are themselves misled by frontline service providers, as in the case of primary education, where official enrolment numbers diverged from survey estimates after funding shifted from user fees to per pupil government grants. Both syndromes highlight the need for incentive compatibility between data systems and funding rules.
Publisher: Routledge _eprint: https://doi.org/10.1080/00220388.2014.968138 KerkoCite.ItemAlsoKnownAs: 10.1080/00220388.2014.968138 2339240:ATP89MMQ 2405685:EHZXJTYM 4656463:NTFGA7D5

Prospective teachers' teaching experience: teacher learning through the use of video - Osmanoglu, Aslihan (Educational Research, 2015)
Background: Future teachers need to observe, interpret and analyse teaching during the initial teacher education period. The use of videoed teaching and learning in teacher education promotes reflection, and analysing videos of teaching is helpful in learning effective classroom practices that prospective teachers mostly do not have the chance to observe during fieldwork experiences. The analysis of videos of teaching can be seen as a way to enhance the development of prospective teachers' professional vision, which, in turn, improves instruction. Purpose: The purpose of this study was to examine prospective teachers' reflections on video examples depicting their own teaching experiences. It aimed to create a professional development environment to facilitate the prospective teachers' reflection on their own videos and those of their peers to improve their professional vision. Sample: This study was conducted with over 200 (in 31 groups) third-year prospective mathematics teachers in a university in Western Turkey. The student teachers, receiving training to teach first- to fourth-grade elementary school pupils, were taking a teaching methods course. Design and methods: In the first week of the semester, the student teachers, working in groups, were assigned mathematics topics to teach the elementary school pupils. During the semester, each group prepared by trying out their activities in front of other student teachers in other groups. At the end of the semester, one student teacher from each group presented a short lesson related to their mathematical topic to the elementary school pupils. This lesson was videotaped, then later it was watched and discussed by the student teachers. Of the student teachers who undertook the teaching in the videos, 22 volunteers agreed to be interviewed. All groups of student teachers provided written reflections on their experience. Selected videos of the class discussions about the videos of teaching were also used for triangulation. The data were analysed to identify the issues the prospective teachers reflected upon. A content analysis technique was employed. Results: The data indicated that the prospective teachers were able to reflect on several issues related to effective teaching, connect their theoretical knowledge to their practice and consider issues related to pupil learning and difficulties. Conclusion: The findings suggested that the use of video, together with discussions between the student teachers, had the potential to create promising learning opportunities for prospective teachers.
Publisher: Routledge, Available from: Taylor & Francis, Ltd. 325 Chestnut Street Suite 800, Philadelphia, PA 19106 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1826519864?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1080/00131881.2015.1117321 2339240:IDCYSM7U 2339240:JN6DATHN 2405685:8R9AMXSP 2405685:UXX82Q2E 2534378:2ENRXCPY 2534378:6ZC4QF9U 2534378:CZGC7EHH
Keywords: Case Method (Teaching Technique); Case Studies; Case-based pedagogy; Content Analysis; Data Analysis; Discussion (Teaching Technique); EDUCATION of student teachers; EFFECTIVE teaching; ELEMENTARY school teachers; ERIC; Current Index to Journals in Education (CIJE); Educational Benefits; Electronic Learning; Elementary Education; Elementary School Teachers; Foreign Countries; Higher Education; Knowledge Base for Teaching; Learning Activities; Mathematics Teachers; Methods Courses; Microteaching; Outcomes of Education; PROFESSIONAL education; Postsecondary Education; Preservice Teacher Education; Preservice Teachers; Reflective Teaching; Student Teacher Attitudes; Student Teachers; TEACHER education; TEACHING methods; TRAINING of student teachers; Teacher Effectiveness; Teaching Experience; Theory Practice Relationship; Turkey; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096187; __finaldtb; class discussions; prospective teacher education; reflection; video case study

Learning through Assistive Devices: A Case of Students with Hearing Impairment - Farooq, Muhammad Shahid; Aasma; Iftikhar, Umaira (Bulletin of Education and Research, 2015)
Present era has introduced persons with disabilities with a range of assistive devices that have rapidly increased their educational, vocational, and frivolous activities. Current descriptive study attempted to explore the effects of assistive devices on the learning of hearing impaired students. A sample of 200 hearing impaired students was selected to identify the assistive devices that are more in use by hearing impaired students. All of the assistive devices commonly used for hearing impairment were included in the study to explore the effects of each on the learning of students with hearing impairment. The mean difference in the learning of students suggested that assistive technologies are overall assistance for the students with hearing impairment and there is no substitute to these devices that could assist them in such a quite differentiated manner. The role of high tech assistive devices as well as low tech devices has been highlighted prominently. The parents of hearing impaired students were also the part of study and found satisfied with the use of assistive devices for their children. It is divulged that there is a need to reduce the cost of assistive devices to be used by the students with hearing impairment.
Publisher: Institute of Education and Research KerkoCite.ItemAlsoKnownAs: 2339240:BMZ8MTPR 2405685:GTZBXLQU
Keywords: Assistive Technology; Costs; Elementary School Students; Foreign Countries; Grade 4; Hearing Impairments; Interpersonal Communication; Parent Attitudes; Program Effectiveness; Quality of Life; Student Needs; ___working_potential_duplicate; ⛔ No DOI found

Learning through Assistive Devices: A Case of Students with Hearing Impairment - Farooq, Muhammad Shahid; Aasma; Iftikhar, Umaira (Bulletin of Education and Research, 2015)
Present era has introduced persons with disabilities with a range of assistive devices that have rapidly increased their educational, vocational, and frivolous activities. Current descriptive study attempted to explore the effects of assistive devices on the learning of hearing impaired students. A sample of 200 hearing impaired students was selected to identify the assistive devices that are more in use by hearing impaired students. All of the assistive devices commonly used for hearing impairment were included in the study to explore the effects of each on the learning of students with hearing impairment. The mean difference in the learning of students suggested that assistive technologies are overall assistance for the students with hearing impairment and there is no substitute to these devices that could assist them in such a quite differentiated manner. The role of high tech assistive devices as well as low tech devices has been highlighted prominently. The parents of hearing impaired students were also the part of study and found satisfied with the use of assistive devices for their children. It is divulged that there is a need to reduce the cost of assistive devices to be used by the students with hearing impairment.
KerkoCite.ItemAlsoKnownAs: 2339240:Z7WED3QU 2405685:L6EEZ9LR
Keywords: Assistive Technology; Costs; Elementary School Students; Foreign Countries; Grade 4; Hearing Impairments; Interpersonal Communication; Parent Attitudes; Program Effectiveness; Quality of Life; Student Needs; ___working_potential_duplicate; ⛔ No DOI found

Education and International Development: An Introduction - McCowan, Tristan; Unterhalter, Elaine (Bloomsbury Publishing, 2015)
'Honorable Mention' 2016 PROSE Award - Education PracticeEducation is fundamental to every aspect of development and there is widespread support across the world for policies that affirm that all children, regardless of their circumstances, have a right to quality schooling. Yet despite concerted efforts from national governments, multilateral organisations and NGOs over many decades we are still far from achieving education for all. In addition, while education can enhance human development, it is also associated with persistent inequalities. Education and International Development provides a comprehensive introduction to the field, giving an overview of the history, influential theories, important concepts and areas of achievement, and presenting a critical reflection on emerging trends in policy, practice and research. With chapters that review key challenges and inspiring initiatives in countries around the globe - focusing on critical issues such as language, conflict and teachers - this book serves both as a companion to graduate studies in international education and a concise reference book for practitioners and educators in the field.
zotzenLib.CopiedFrom: 2339240:QIPYJY2A KerkoCite.ItemAlsoKnownAs: 2339240:QIPYJY2A 2405685:7BCHIHFK
Keywords: Education / Comparative; Education / Multicultural Education

Cultivating a personal learning network that leads to professional change - Stewart, Benjamin L. (Northcentral University, 2015)
Teacher professional development opportunities in Mexico are currently lacking. The traditional approaches of professional development such as workshops and conferences are commonplace but do little to bridge the gap between abstract concepts about teaching and learning and the practicalities teachers face in the classroom. The purpose of this qualitative multiple case study was to describe how ideas, materials, and social interactions form a PLN through online, informal pedagogical dialogues among English language educators as it relates to professional learning. The five participants of this study were selected from a total of 10 based on their willingness to complete an informed consent form, complete an initial online survey, interact with other professionals publically online, and participate in a final interview. The online survey contained demographic information about each case and included both open and closed items; a content analysis was done on public interactions that tool place online; and a final in-depth interview used open questions to inquire about how respective PLNs changed over time. All data was coded, categorized, and placed into themes based on the ideational, material, and social aspects of each PLN. The findings show that professional knowledge, skills sets, and overall dispositions emerge in unique ways based on how ideas, technologies, and personal contacts interrelate with each other over time, and that an individual’s PLN provides unanticipated benefits when sharing publicly online.
ISBN: 978-1-339-39148-9 Publication Title: ProQuest Dissertations and Theses 3746019 Loc in Archive 1758252241 KerkoCite.ItemAlsoKnownAs: 2405685:TCB3AT84 2534378:8ZJEL8UE 2534378:HG5HYUVR
Keywords: 0444:Foreign language education; 0449:Educational leadership; 0710:Educational technology; Actor-network theory; Complexity; Content analysis; Education; Educational leadership; Educational technology; English; Foreign Language; Learning; Personal learning network; Polls & surveys; Teacher education; __:import:01; __:match:final; __:matched; __:study_id:2096277; __finaldtb

Challenges and opportunities for teacher professional development in interactive use of technology in African schools - Hennessy, Sara; Haßler, Bjoern; Hofmann, Riikka (Technology, Pedagogy and Education, 2015)
This article examines the supporting and constraining factors influencing professional learning about interactive teaching and mobile digital technology use in low-resourced basic schools in sub-Saharan Africa. It draws on a case study of iterative development and refinement of a school-based, peer-facilitated professional learning programme (‘OER4Schools’) that integrated use of mobile technologies, digital open educational resources and interactive pedagogy. The research and development involved teachers in three Zambian primary schools and culminated in an extensive multimedia resource. Using an ecological framework, factors emerging were characterised at three levels: teacher, school, and the wider community and policy context. They include school organisation and leadership, teacher motivation and perceptions of opportunities for professional learning and change, teacher views of pupil capabilities, availability of resources, teacher collaboration, and viewpoints of parents and policymakers. [ABSTRACT FROM PUBLISHER]
Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.ebscohost.com/login.aspx?direct=true&db=bri&AN=111289127&site=ehost-live&scope=site KerkoCite.ItemAlsoKnownAs: 10.1080/1475939X.2015.1092466 10/gfv5xz 2129771:L2HUHYLN 2339240:24LHAF5C 2339240:K9R22K2F 2339240:WV3XY5NW 2405685:6ZLKKKH7 2405685:8V49PM4G 2405685:KILQYYBU 2405685:SXKPQUJ5 2534378:6TMRG3EP 2534378:BF6PBW3F 2534378:QQ6BVI89
Keywords: ADULTS; AFRICA; Article; CAREER development; Digital Technology; EDUCATION; EDUCATIONAL technology research; Interactive Pedagogy; Open Educational Resources; PRIMARY school teachers; Sub-Saharan Africa; Zambia; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2099892; __finaldtb; digital technology; interactive pedagogy; open educational resources; sub-Saharan Africa; teacher professional development

The effects of a technology-aided learning environment on the improvement of a primary special education school - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people’s expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming ‘learning’ or ‘effective’ schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers’ functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed. Key words: School development, technology, innovation, hearing impaired.
KerkoCite.ItemAlsoKnownAs: 10.5897/ERR2015.2523 2339240:9SHHNJCH 2405685:WQ7ZLZVW
Keywords: ___working_potential_duplicate

Community outreach projects as a sustainable way of introducing information technology in developing countries - Zlotnikova, Irina; van der Weide, Theo (International Journal of Education and Development using Information and Communication Technology (IJEDICT), 2015)
The paper describes an approach to the sustainable introduction of IT in developing countries based on international collaboration between students taking the form of a knowledge bridge. The authors consider the challenges for introducing information technologies in developing countries; one of these is lack of reading materials ultimately leading to lack of reading skills in pupils and poor overall performance. A theoretical framework for the sustainable introduction of IT is proposed. It comprises the following components: (1) the model of a knowledge bridge, (2) the managerial model of the interactions between key stakeholders, and (3) the model of impact of a Community Outreach Project (COP) on target schools. The proposed models have been mapped to the widely adopted DPSIR framework used in sustainable development studies. As a case study, the authors discuss the E-readers Project run in two primary schools in Northern Tanzania. The paper also demonstrates how interaction and collaboration between Tanzanian and Dutch students was organized during preparatory stage and project implementation. The paper concludes with general recommendations on how to run a sustainable IT-based COP. These recommendations have been drawn from the analysis of the COP experience in the developing country, namely Tanzania.
KerkoCite.ItemAlsoKnownAs: 2339240:5ZZ2V4QY 2405685:PJTVSTPT
Keywords: ⛔ No DOI found